ISM NAKIRAH (NOMINA INDEFINIT) DANISM MA’RIFAH (NOMINA DEFINIT) DALAM TEKS BACAAN AL-‘ARABIYYAH BAINA YADAIK JILID 4 JUZ 2(ANALISIS SINTAKSIS): ISIM NAKIRAH (INDEFINITE NOMINA) AND ISIM MA'RIFAH (DEFINITE NOMINA) IN THE AL-'ARABIYYAH BAINA YADAIK TEXTBOOK VOLUME 4 PART 2 (SYNTAXIC ANALYSIS) - Azka, Ianah Millati; Ahmad Hasyim, Mohamad Yusuf (Lisanul Arab: Journal of Arabic Learning and Teaching, 2025)
Studying nahwu means studying the rules governing the usage of Arabic sentences, encompassing their structure, position, and grammatical markers. In nahwu studies, understanding ism nakirah (indefinite noun) and ism ma’rifah (definite noun) is crucial due to the significant impact of the article "الْ" on sentence meaning. This thesis discusses ism nakirah and ism ma’rifah within the text "Al-‘Arabiyyah Baina Yadaik Volume 4 Part 2 (Syntactic Analysis)". The research aims to identify the types of ism nakirah and ism ma’rifah, and analyze their syntactic functions and grammatical markers in the mentioned text. This is a qualitative study utilizing a library research design. The data consist of ism nakirah and ism ma’rifah occurrences in "Al-‘Arabiyyah Baina Yadaik Volume 4 Part 2". Research instruments include data cards and summary sheets, with data collection techniques involving reading and writing. Purposive sampling is employed to select data samples aligned with the research objectives. Data analysis techniques encompass data collection, reduction, presentation, and conclusion drawing. Findings reveal 2,555 instances of ism nakirah and ism ma’rifah in the text. Through purposive sampling, 100 data samples were selected for analysis, comprising 25 instances of ism nakirah and 75 instances of ism ma’rifah. Among the latter, the researcher identified 15 instances of ism dlamīr, 11 of ism ‘alam, 10 of ism isyārah, 10 of ism maushūl, 14 of ism ma’rifah prefixed with "al", 14 of ism id̲l̲āfah with another ism ma’rifah, and 1 instance of ism munad̲ā nakirah maqshūd̲ah. Syntactic functions in the study include 37 instances of raf’, 24 of nashb, and 39 of jarr. The nature of their i’rāb includes 62 instances of ism mu’rab and 38 instances of ism mabnī. Among the 62 mu’rab instances, 21 are marked with ḍamma, 17 with faṭḥah, and 24 with kasrah. Meanwhile, the 38 mabnī instances consist of 4 with ḍamma, 9 with faṭḥah, 4 with kasrah, and with 21 sukun.